Islam dan Perubatan: Satu Kajian Umum Mengenai Tibb Nabawi - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 1998)
The article attempts to elaborate the concept of medicine in Islam based on al-Tibb al-Nabawi. It tries to explain that Islam does not merely emphasize on the question of hereafter alone but also on health, treatment as well as prevention. This is a clear proof that Islam is in line with modern medicine which in one way or another indicates that Islam itself is a way of life.